A second exopolysaccharide of Rhizobium meliloti strain SU47 that can function in root nodule invasion. - Zhan, H J (1989)
Rhizobium meliloti strain SU47 produces the calcofluor-binding exopolysaccharide, succinoglycan, that is required for alfalfa root nodule invasion. Strains derived from R. meliloti SU47 secreted an acidic exopolysaccharide, EPSb, that replaced succinoglycan in nodule invasion. EPSb, which has not formerly been identified among the Rhizobiaceae, consisted of the repeating unit 4,6-O-(1-carboxyethylidene)-alpha-D-Galp1----3(X-O-Ac)-beta-D-G lcp1----3. EPSb synthesis occurred either in strains containing a mutation in a locus designated mucR or in strains with a recombinant cosmid pMuc. mucR mapped slightly counterclockwise from pyr49 on the chromosome, while pMuc contained genes mapping to the megaplasmid pRmeSU47b. In exoA, -F, and -H mutants, which are deficient in normal succinoglycan secretion and nodule invasion, a transposon Tn5 insertion in mucR or the presence of pMuc resulted in EPSb secretion and a restoration of nodule invasion on Medicago sativa and Melilotus alba. Mutants in exoB and exoC were incapable of succinoglycan and EPSb secretion as well as nodule invasion. A mutant that secreted succinoglycan but was incapable of EPSb secretion invaded nodules normally.